RECONSTRUCTIVE SURGERY OF HEAD AND NECK BURN SCARS USING TISSUE EXPANDERS - Malik, Abdul Khaliq; Aimen, Syeda; Javed, Naima; Ud Din, Hameed; Fazid, Sheraz; Khan, Abdul Jalil; Ul-Haq, Zia (Annals of Allied Health Sciences, 2019)
OBJECTIVE: Grotesque head and neck scars cause significant restriction of neck movement while facial scars are a cause of social dejection. We aimed to correct these unsightly scars using tissue expanders. METHODS: This descriptive prospective study was conducted on 5 patients with extensive burn scars on neck and head presented in Plastic Surgery OPD from January 2017 to December 2018. Tissue expanders were placed in these patients after adequate tissue dissection. RESULTS: Out of the 5 cases in study 2 had scald burns, 2 had flame burns and one had chemical burn and were mostly male (n=4). The scar was mostly in the head (1 in scalp, 2 on face). Rectangular expander was used in three cases mostly in the neck region while crescent-shaped was employed in the scalp. One cylindrical was placed in the facial region. Tissue expansion started 2-3 weeks depending on wound healing. Color matching was favorable in all the cases of successful tissue expansion and coverage. After adequate tissue expansion, expander was removed and lesion excised. Complication being expander extrusion was observed in one case in which expander was removed and flap was advanced to cover the defect. CONCLUSIONS: Using tissue expander in tissue reconstruction of extensive neck and facial burn scars results in desirable outcomes in terms of tissue matching and patient satisfaction. However, caution should be exercised to prevent infection, dehiscence and prosthetic extrusion.